SISTEM INFORMASI ADMINISTRASI PENJUALAN JASA PADA PERCETAKKAN EKAMEDIA DENGAN ANALISIS PENERAPAN METODE SWOT - Sri Tita Faulina; Rika Bherta (Jurnal Informatika dan Komputer (JIK), 2019)
The purpose of this research is to produce an Information System application that can manage Sales Service Administration data, provide convenience in data processing, search data Inventory and Sales of Services that exist in the Printing Ekamedia.This study uses several methods to obtain the data needed, namely Observation Method, Reference Method and Interview Method.The results of this study were conducted in the form of Information Services Administration Sales Services at Ekamedia Printing. This application consists of 6 menus, such as Files, Input Data, Transactions, Search Reports, Admin and Logout